A compact and facile microfluidic droplet creation device using a piezoelectric diaphragm micropump for droplet digital PCR platforms. Issue 20 (24th July 2017) - Okura, Naoaki; Nakashoji, Yuta; Koshirogane, Toshihiro; Kondo, Masaki; Tanaka, Yugo; Inoue, Kohei; Hashimoto, Masahiko
Abstract: We have exploited a compact and facile microfluidic droplet creation device consisting of a poly(dimethylsiloxane) microfluidic chip possessing T‐junction channel geometry, two inlet reservoirs, and one outlet reservoir, and a piezoelectric (PZT) diaphragm micropump with controller. Air was evacuated from the outlet reservoir using the PZT pump, reducing the pressure inside. The reduced pressure within the outlet reservoir pulled oil and aqueous solution preloaded in the inlet reservoirs into the microchannels, which then merged at the T‐junction, successfully forming water‐in‐oil emulsion droplets at a rate of ∼1000 per second with minimal sample loss. We confirmed that the onset of droplet formation occurred immediately after turning on the pump (<1 s). Over repeated runs, droplet formation was highly reproducible, with droplet size purity (polydispersity, <4%) comparable to that achieved using other microfluidic droplet preparation techniques. We also demonstrated single‐molecule PCR amplification in the created droplets, suggesting that the device could be used for effective droplet digital PCR platforms in most laboratories without requiring great expense, space, or time for acquiring technical skills.